Pengaruh Game Edukasi “Secil” terhadap Keterampilan Membaca Permulaan Anak Usia Dini di Taman Kanak-kanak - Rahmadani, Putri; Muryanti, Elise (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Skills of early reading are very urgent to be stimulated in early ages. The purpose of research is to reveal the